Bridging Scholarship and Practice: 20 Years of the Public International Law and Policy Group - McGonigle Leyh, Brianne; Fraser, Julie (Utrecht Journal of International and European Law, 2017)
When the Editor-in-Chief of the Utrecht Journal of International and European Law (UJIEL) approached us with the possibility of guest editing a special issue related to public international law and policy, we felt the timing could not have been better. As academics at Utrecht University with the Netherlands Institute of Human Rights and Montaigne Centre for Judicial Administration and Conflict Resolution, we felt that a theme linking the world of lawyers with that of policymakers was important in order to examine the role of law in protecting human rights and security. Moreover, as Senior Counsel with the Public International Law & Policy Group (PILPG), which celebrated its 20-year anniversary in 2016, we welcomed the idea to link academic scholarship with the work of PILPG. After all, PILPG’s founders, Professor Paul Williams and Professor Michael Scharf, have themselves acted as bridges between scholarship and practice for years. As a result, this special edition is not only intended to highlight the extraordinary work carried out by PILPG on issues of law and policy around the world, but also to emphasise the importance of linking scholarship with practice and addressing contemporary issues impacting the world in which we live. PILPG’s motto ‘lawyering peace’ requires reflection on the role that law can play in helping to bring about the peaceful resolution of serious problems affecting individuals and societies as a whole. This special edition of UJIEL, addressing a variety of themes, does just that.